The culture of international arbitration and the evolution of contract law - Karton, Joshua D. H. (Oxford : Oxford University Press, 2013)
Examining a developing culture of international commercial arbitration and the implications for the evolution of contract law, this book includes case studies and analysis from interviews with international arbitrators and national court judges, and identifies trends to explain and predict arbitration decisions on issues of substantive law.
Description based on online resource; title from home page (viewed on Apr. 29, 2013).
Includes bibliographical references and index.
Keywords: International commercial arbitration; International commercial arbitration -- Cases; Contracts (International law); Contracts (International law) -- Cases